Production and toxicity evaluation of Rhamnolipids produced by Pseudomonas strains on L6 and Hepg2 cells - Arularasu Muthaliar Tamothran,; Vigneswari Sevakumaran,; Kesaven Bhubalan, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Biosurfactant rhamnolipid (RL) production using renewable resource is gaining attraction for commercial application. In this study, RL produced from three different strains of Pseudomonas using glycerol as a carbon source was used to evaluate toxicity towards rat skeletal muscle (L6) and liver cancer (HepG2) cells. In the present study, Pseudomonas aeruginosa PAO1 produced the highest concentration of RL (1.53 ± 0.28 g/L) and able to reduce the surface tension (ST) value of water the lowest (29.1 ± 0.5 mN/m). Toxicity evaluation using MTT assay indicated that RL produced does not have a cytotoxic effect towards both cell lines except where 50% inhibition concentration (IC50) was detected for HepG2 only at high concentration (100 µg/mL) for RL produced by P. aeruginosa PAO1. The RL produced by strains in this study is nontoxic with good ST reducing ability that has potential applications in food, cosmetics and pharmaceutical sector.